2014
DOI: 10.1111/pim.12120
|View full text |Cite
|
Sign up to set email alerts
|

Wuchereria bancrofti 20/22 a homologue of abundant larval transcript L3 stage filarial antigen: molecular and immunological characterization

Abstract: The chromadorea abundant larval transcript (ALT) family of proteins contains ALT one of the most studied putative vaccine candidate in experimental filariasis. This study reports the characterization of Wuchereria bancrofti 20/22 (Wb20/22) as a member of chromadorea, the ALT family of proteins from the L3 stage of W. bancrofti. The high reactivity with serum from the endemic normal (EN) population suggests that Wb20/22 could be a target of elicit protective immunity. The glutamic acid-rich region of Wb20/22 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Micropore chamber method was carried out 1 week after final immunization to evaluate the immunoprophylactic efficacy of FEP, which is a widely used technique for protection study . The experiments were performed three times with five animals per group in each experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Micropore chamber method was carried out 1 week after final immunization to evaluate the immunoprophylactic efficacy of FEP, which is a widely used technique for protection study . The experiments were performed three times with five animals per group in each experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Vaccination with a fusion protein of Bm-103 and Bm-RAL-2 or concurrently, induced a significant worm reduction of 61% and 42% in gerbils respectively (Arumugam et al, 2016). The prophylactic efficacy of Wb20/22 protein without acidic domain (WOAD) conferred 62.26% protection which was higher than 49.82% of Wb20/22 and 54.78% of Wb20/22 without signal sequence (WOSS) (Aparnaa et al, 2014). Anugraha et al reported the prophylactic efficacy of the filarial epitope protein (FEP), a chimera of selective epitopes from thioredoxin (TRX), several epitopes from transglutaminase (TGA) and abundant larval transcript-2 (ALT-2) indicating a significant protection (69.5%) against filarial L3 larvae in jirds (Anugraha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…malayi , and with higher levels of seropositivity against W . bancrofti ALT-2 in endemic normal patients relative to those who are microfilaremic or experiencing chronic pathology [ 10 , 45 , 50 ]. It is potentially consistent with reports of immunity to a 23 kDa antigen corresponding with microfilaremia relative to overt pathology in loiasis patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%